2003
DOI: 10.1038/nm899
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of P-selectin and PSGL-1 generates microparticles that correct hemostasis in a mouse model of hemophilia A

Abstract: High plasma levels of soluble P-selectin are associated with thrombotic disorders and may predict future cardiovascular events. Mice with high levels of soluble P-selectin have more microparticles in their plasma than do normal mice. Here we show that chimeras of P-selectin and immunoglobulin (P-sel-Ig) induced formation of procoagulant microparticles in human blood through P-selectin glycoprotein ligand-1 (PSGL-1; encoded by the Psgl1 gene, officially known as Selpl). In addition, Psgl1-/- mice produced fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
222
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(231 citation statements)
references
References 43 publications
7
222
0
2
Order By: Relevance
“…Based on these findings, we suggested that a physiological activity of platelet TFPI is the inhibition of blood-borne TF procoagulant activity accumulating within a growing thrombus (24). This hypothesis is supported by the work of Hrachovinová and coworkers, who demonstrated that TF-bearing microparticles, generated by infusion of P-selectin-Ig chimeras, corrected the plasma clotting time and tail vein bleeding time of F8 −/− mice (28). In addition, Massberg and coworkers demonstrated that following vascular injury, TFPI is captured by externalized neutrophil nucleosomes and then efficiently degraded by neutrophil serine proteases, producing localized intravascular thrombosis (29).…”
Section: Discussionmentioning
confidence: 65%
“…Based on these findings, we suggested that a physiological activity of platelet TFPI is the inhibition of blood-borne TF procoagulant activity accumulating within a growing thrombus (24). This hypothesis is supported by the work of Hrachovinová and coworkers, who demonstrated that TF-bearing microparticles, generated by infusion of P-selectin-Ig chimeras, corrected the plasma clotting time and tail vein bleeding time of F8 −/− mice (28). In addition, Massberg and coworkers demonstrated that following vascular injury, TFPI is captured by externalized neutrophil nucleosomes and then efficiently degraded by neutrophil serine proteases, producing localized intravascular thrombosis (29).…”
Section: Discussionmentioning
confidence: 65%
“…Whether the minute amounts of MP-associated TF activity observed in the plasma of healthy volunteers (0.5-4 fM) are sufficient to stimulate fibrin formation is unknown; TFdependent FXa generation might be too low to overcome the natural thresholds of the anticoagulant systems [35]. In patients with progressive mucinous cancer tumor-derived MUC1 + -MP may display enhanced binding to P and/or L selectin on platelets or other hematopoietic cells or on MP derived from such cells [36,37]. Study of the co-expression of MUC1 and platelet antigen CD61 on MP by confocal immunofluorescence microscopy revealed that a small part of circulating MP seemed to result from fusion of cellular vesicles originating from malignant epithelial cells and platelets in patients with disseminated breast and pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy controls and non-disseminated breast cancer patients were all alive at the end of the study, with a median follow-up of 36 months (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Median survival after collection of the blood samples was 12 months (range: 1-44) in metastatic breast cancer patients and 3 months (range: 1-13) in pancreatic cancer patients.…”
Section: Cancer Patients and Controlsmentioning
confidence: 99%
“…26 TF expressed on the surface of PMV initiates coagulation by activating factor VII to recruit platelets and initiate the pathway to thrombus formation in the response to vascular injury. 27 However increased TF expression does not always correlate with increased coagulation, suggesting that other factors are similarly important. 22,28 Integrin α 11b β 3 , another receptor expressed on the outer PMV surface, has a role in binding PMV to fibrinogen to cause platelet adhesion.…”
Section: Procoagulant Activitymentioning
confidence: 99%